ALAT PENGUKUR SUHU TUBUH MANUSIA TANPA KONTAK FISIK BERBASIS ARDUINO - ojik, ahmad tarmuzi; Wafiah Murniati; Muhammad Fauzi Zulkarnaen (Lembaga Pengembangan Kinerja Dosen, 2022)
Abstract Measurement of human body temperature can be measured using a clinical thermometer. Types of thermometers that already exist today include an analog thermometer and a digital thermometer. In general, this tool takes the fastest time of one to two minutes to get a body temperature value, then the scarcity and drastic increase of the tool during the pandemic make the tool rarely found. In this research, a tool is designed that can be used to determine the value of human body temperature in a short time and obtain accurate readings. Usingg an infrared sensor with the MLX90614 series which is combined with Arduino Uno, ultrasonic sensor, buzzer, led, and a 16x2 LCD screen display is a way that is used to make a body thermometer without physical contact. The research method used is by collecting data, analyzing requirements, designing hardware, and software as well as testing or testing that is carried out on the tool made to find out whether the tool has been running and working as expected.